Bradycardia during sleep apnea. Characteristics and mechanism. - Zwillich, C (1982)
To determine the characteristics of and mechanisms causing the bradycardia during sleep apnea (SA), both patients with SA and normals were studied. Evaluation of six consecutive SA patients demonstrated that bradycardia occurred during 95% of all apneas (central, obstructive, and mixed) and became marked with increased apnea length (P less than 0.01) and increased oxyhemoglobin desaturation (P less than 0.01). Heart rate slowed 9.5 beats per minute (bpm) during apneas of 10-19 s in duration, 11.4 bpm during 20-39s apneas, and 16.6 bpm during 40-59-s apneas. Sleep stage had no effect unexplained by apnea length or degree of desaturation. Oxygen administration to four SA patients completely prevented the bradycardia although apneas lengthened (P less than 0.05) in three. Sleeping normal subjects did not develop bradycardia during hypoxic hyperpnea but, instead, HR increased with hypoxia in all sleep stages, although the increase in HR was not as great as that which occurred while awake. Breath holding in awake normals did not result in bradycardia during hyperoxia (SaO2 = 99%), but was consistently (P less than 0.01) associated with heart rate slowing during room air breath-holds (-6 bpm) at SaO2 = 93%, with more striking slowing (-20 bpm) during hypoxic breath-holds (P less than 0.01) at SaO2 = 78%. Breath holding during hyperoxic hypercapnia had no significant effect on rate. Breath holding in awake SA subjects demonstrated similar findings. We conclude that the bradycardia of SA is a consistent feature of apnea and results from the combined effect of cessation of breathing plus hypoxemia.